Legal accomodation of Islamic banking in Bosnia and Herzegovina : a comparative appraisal in the European context - Trakic, Adnan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2012)
The Islamic banking industry in Bosnia and Herzegovina (B&H) is part of the banking sector which has tremendous potential. In order for the industry to be able to prosper in the future, it needs to have an adequate legal framework within which it will operate and by which it will be duly protected. Furthermore, the legal framework for the Islamic banking industry in B&H needs to be devjsed in the European context since Bosnia is a potential candidate for European Union (EU) membership. The Islamic banking industry in B&H does not have an adequate legal framework, and the only existing Islamic bank in the country operates within the conventional banking framework. In addition, the dispute settlement mechanism for Islamic banking cases is not adequate since the cases are being heard before the civil court judges who do not consider the underlying Islamic nature of the transactions and who lack sufficient knowledge about Islamic banking. The existing Law on Banks of the Federation of Bosnia and Herzegovina (FB&H) limits the application of some very significant Islamic banking products which are normally used by Islamic banks around the world. In the past, there was an attempt to amend the Law on Banks of the FB&H but the amendment has not passed into law. This research offers constructive suggestions for the creation of an adequate legal framework for the Islamic banking industry which would be effectively protected by an adequate dispute settlement mechanism. In order to offer practical solutions for the establishment of the legal framework for the Islamic banking industry in B&H, the researcher has studied the obstacles that the industry, and the amendment of the Law on Banks of the FB&H, are facing in B&H. In that regard, an in-depth analysis of the._official letters exchanged by the influential officials locally and internationally about the passing of the amendment to the Law on Banks of the FB&H has been done. Furthermore, this is a comparative research whereby the experience of two countries, the UK and Malaysia, in devising an adequate legal framework for the Islamic banking industry has been analyzed with the intent of applying the relevant experience in the context of B&H. The adequate legal framework for Islamic banking in B&H needs to be in line with three sets of laws, namely, local banking laws i.e. the Law on Banks of the FB&H, EU Directives and policies, and Sharf'ah. The adequate dispute settlement mechanism for Islamic banking cases in B&H would mean the upholding of the underlying Sharf'ah principles of the transactions by the civil court judges or the establishment of a commercial tribunal which would specifically deal with Islamic banking disputes. This research is a contribution towards further development of the Islamic banking industry in B&H specifically, and in the EU in general.